Prevalensi gondok endemik pada anak-anak sekolan dasar di kecamatan jatipuro - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
ABSTRAK A study of endemic goiter prevalence among primary school children was conducted in the Jatipuro Sub-district, Karanganyar District, Central Java. Between 1981 - 1985 a health centre lipiodolization and iodized-salt supplementation program was instituted in 10 villages of this sub-district. Lipiodol injection were administered to females who were 0 - 35 years old, had the disease or were over 35 years but pregnant, and males who were 0 - 14 years old or had the disease. The purpose of this study was to evaluate the effectiveners of the program. All primary school children (5, 102) from grade Ito VI of the 10 villages were interviewed and examined according to the Perez et a!. method. The disease was present in 13 students, or 0,25%, which means that the area is now non-endemic.